Introduction to criminal justice information systems - Ioimo, Ralph (CRC Press/Taylor & Francis, 2016)
Introduction to Criminal Justice Information Systems gives an overview of the various software systems and technologies currently used in the criminal justice environment. The book covers a variety of topics critical to each member of the criminal justice system: police, prosecutor, courts, and corrections.